Robust multiple sensor fault-tolerant control for dynamic non-linear systems: Application to the aerodynamical twin-rotor system - Pazera, Marcin; Buciakowski, Mariusz; Witczak, Marcin (Zielona Góra: Uniwersytet Zielonogórski)
The paper deals with the problem of designing sensor-fault tolerant control for a class of non-linear systems. The scheme is composed of a robust state and fault estimator as well as a controller. The estimator aims at recovering the real system state irrespective of sensor faults. Subsequently, the fault-free state is used for control purposes. Also, the robust sensor fault estimator is developed in a such a way that a level of disturbances attenuation can be reached pertaining to the fault estimation error.
Keywords: fault-tolerant control; sensor faults; fault estimation; twin-rotor system